CERITA SEBAGAI METODE PENANAMAN NILAI-NILAI MORAL BAGI ANAK - B, Chaeruddin (Inspiratif Pendidikan, 2016)
A story is a narrative occurred in the past both of which actually happened and imaginary. Stories from ancient existing among the people and passed on orally. The story contains a variety of moral values and unbiased advice such as honesty, responsibility, courage, defending the truth, solidarity, obedience, solidarity, hard work, and so on. Besides, the story also contains entertainment, so it is often used to entertain children who experienced trauma in refugee camps for floods, landslides, fires and so on. The story is very interesting for children as well as adults. Therefore, parents or grandparents make it as a method of educating children or grandchildren and make as bedtime for their children and grandchildren. The effectiveness of story is not inferior to other methods using technology in educating children. Stories can increase the power of thought and imagination, and train the children’s emotional. Having many benefits of stories for children (3-12 years), it needs to be intensified as a method of learning, especially for preschool and elementary school level.